Diffusion‐weighted imaging of the prostate: Comparison of b1000 and b2000 image sets for index lesion detection. Issue 3 (31st January 2013) - Rosenkrantz, Andrew B.; Hindman, Nicole; Lim, Ruth P.; Das, Kasturi; Babb, James S.; Mussi, Thais C.; Taneja, Samir S.
<x xml:space="preserve">Abstract</x> Purpose: To compare tumor detection on acquired diffusion‐weighted (DW) images and apparent diffusion coefficient (ADC) maps, obtained using b‐values of 1000 s/mm2 and 2000 s/mm2, using radical prostatectomy as the reference. Materials and Methods: In all, 29 prostate cancer patients who underwent 3T magnetic resonance imaging (MRI) including DW imaging using b‐values of 1000 s/mm2 and 2000 s/mm2 were included. Two radiologists independently evaluated four image sets during different sessions and recorded the location and diameter of the dominant lesion: DW images acquired using b‐values of 1000 s/mm2 and 2000 s/mm2 and ADC maps calculated using maximal b‐values of 1000 s/mm2 and 2000 s/mm2. Findings were correlated with the location and diameter of the dominant lesion at prostatectomy. Tumor‐to‐PZ contrast was also calculated, unblinded to pathology. Results: Both readers achieved significantly higher sensitivity for DW images obtained using a b‐value of 2000 s/mm2 than 1000 s/mm2 (P < 0.001), although there was no difference in sensitivity between ADC maps calculated using the two b‐values (P ≥ 0.309). Tumor‐to‐PZ contrast was higher for DW images using a b‐value of 2000 s/mm2 (P = 0.067), although it was not different between the two corresponding ADC maps (P = 0.544). For both readers, correlations with tumor diameters were higher for either ADC map (r = 0.59–0.73) than for either acquired DW image set (r = 0.03–0.57). Conclusion: Use of a b‐value of 2000 s/mm2 compared with a b‐value of 1000 s/mm2 resulted in improved tumor sensitivity and higher tumor‐to‐PZ contrast on the acquired DW images, although performance of the ADC maps corresponding with the two b‐values was similar. Correlation with tumor size was greater for either ADC map than for either acquired DW image set. J. Magn. Reson. Imaging 2013;38:694–700. © 2013 Wiley Periodicals, Inc.